Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.

Repurposing of a drug scaffold: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, Remya; Shingare, Rahul D.; Kumar, Vinod; Anand, Amitesh; Swetha, B.; Veeraraghavan, Sridhar; Viswanadha, Srikant; Ummanni, Ramesh; Gokhale, Rajesh S.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2016)
The structural similarity between an MmpL3 inhibitor BM212, and a cannabinoid receptor modulator rimonabant, prompted us to investigate the anti-tubercular activity of rimonabant and its analogues. Further optimization, particularly through incorporation of silicon into the scaffold, resulted in new compounds with significant improvement in anti-tubercular activity against Mycobacterium tuberculosis (H37Rv). The sila analogue 18a was found to be the most potent antimycobacterial compound (MIC, 31 ng/mL) from this series with an excellent selectivity index. (C) 2016 Elsevier Masson SAS. All rights reserved.